A quick-setting and quick-hardening fly ash foam concrete and a preparation method thereof
Patent Information
- Application Number
- CN202510348670.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-03-24
AI Technical Summary
[0004]本发明的目的在于,提供一种快凝快硬粉煤灰泡沫混凝土及其制备方法,以解决泡沫混凝土凝结时间慢、强度低的问题
[0023]1、本发明在1200~1250℃下煅烧的硅酸二钙-氧化钙复合胶凝材料,其中硅酸二钙的尺寸为1μm,而传统的硅酸盐水泥熟料中硅酸二钙尺寸超过10μm,较小的尺寸有利于C2S水化硬化,提高泡沫混凝土的强度;并且硅酸二钙-氧化钙复合胶凝材料中CaO的尺寸为10μm左右,消解速度快,生成Ca(OH)2凝胶,放出大量热量,促进料浆稠化,稳定气泡。
Smart Images

Figure CN119977510B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a fast-setting and fast-hardening fly ash foamed concrete and its preparation method. Background Technology
[0002] Foamed concrete refers to lightweight, microporous concrete made by physically creating foam from a foaming agent, then adding the foam to a slurry composed of cement, admixtures, additives, and water, followed by mixing, pouring, and curing. Foamed concrete possesses low self-weight, high fluidity, low aggregate content, controllable low strength, and excellent thermal insulation properties. Ensuring the stability of air bubbles in fresh foamed concrete is crucial for obtaining foamed concrete with superior pore morphology and properties. The stability of air bubbles in fresh concrete determines the pore morphology and distribution of hardened foamed concrete, thus affecting the density, permeability, thermal insulation, and mechanical properties of foamed concrete (especially at ultra-low densities). However, in unstable fresh foamed concrete, air bubbles will continue to destabilize until the slurry hardens. This bubble instability leads to the formation of coarse, uneven pores in the foamed concrete, and even partial or complete collapse.
[0003] To shorten the setting time of freshly mixed foamed concrete and stabilize air bubbles, Chinese invention patent "A High-Strength Foamed Concrete and its Preparation Method" (application number CN202211705709.2) uses sulfoaluminate cement as a cementitious material and mixes in foam at an ultra-low water-cement ratio to prepare high-strength foamed concrete. Chinese invention patent "A Lightweight Thermal Insulation Foamed Concrete and its Preparation Method" (application number CN202410145839.8) effectively shortens the setting time and improves the strength of concrete by selecting silicate cement, calcium magnesium phosphate cement, and calcium silicate cement with a compressive strength of 42.5 or higher as base materials, combined with lightweight aggregates and optimizing additives. Chinese invention patent "A Novel Foamed Concrete Preparation Method" (application number CN202210895977.9) uses a novel special cementitious material and sulfoaluminate cement as cementitious materials to shorten the setting time. Although the above methods can effectively shorten the setting time of foamed concrete, they require a large amount of special cement, resulting in poor economic efficiency. Summary of the Invention
[0004] The purpose of this invention is to provide a fast-setting and fast-hardening fly ash foamed concrete and its preparation method, so as to solve the problems of slow setting time and low strength of foamed concrete.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] On one hand, a fast-setting and fast-hardening fly ash foamed concrete is provided, comprising powder, water, water-reducing agent, and foaming agent; the powder comprises the following components by mass percentage: 26-30 wt% dicalcium silicate-lime composite cementitious material, 5-12 wt% aluminate cement clinker, 5-12 wt% dihydrate gypsum, and 50-60 wt% fly ash; the amount of water is calculated according to a water-to-material ratio of 0.24-0.30; the dosage of the water-reducing agent is 0.8-1.2 wt‰ of the powder mass; the foaming agent is used to prepare foam, and the volume of foam added is based on the bulk density of the foamed concrete.
[0007] Furthermore, the dicalcium silicate-lime composite cementitious material comprises the following mineral components by mass percentage: C2S: 50-62wt%, CaO: 30-36wt%, C3A: 5-10wt%, C4AF: 3-4wt%.
[0008] Furthermore, the dicalcium silicate-lime composite cementitious material is made by calcining low-grade limestone and waste soil cakes at high temperature (1200–1250℃, 20–60 min). The clinker obtained from calcination is then ground to obtain a specific surface area of 330–350 kg / m². 2 The mass of the dicalcium silicate-lime composite cementitious material; the mass of the low-grade limestone and waste soil briquettes is calculated based on the mineral composition of the dicalcium silicate-lime composite cementitious material according to the Bouger formula.
[0009] Furthermore, the low-grade limestone has a loss on ignition of 40.13±2wt% and comprises the following mineral components by mass percentage: SiO2: 6.04±2wt%, Al2O3: 1.77±2wt%, Fe2O3: 0.73±2wt%, CaO: 49.00±2wt%, MgO: 1.10±2wt%.
[0010] Furthermore, the waste soil has a loss on ignition of 17.00±2wt% and comprises the following mineral components by mass percentage: SiO2: 43.60±2wt%, Al2O3: 13.67±2wt%, Fe2O3: 21.51±2wt%, CaO: 1.85±2wt%, MgO: 2.29±2wt%.
[0011] Furthermore, the aluminate cement clinker comprises the following mineral components by mass percentage: CA: 31-49 wt%, CA2: 23-36 wt%, C2AS: 28-33 wt%.
[0012] Furthermore, the alkalinity coefficient A of the aluminate cement clinker m It ranges from 0.9 to 1.0.
[0013] Furthermore, the density of the foamed concrete slurry is 1900–2000 kg / m³. 3 .
[0014] Furthermore, the water-reducing agent is a polycarboxylate water-reducing agent; the foaming agent is one of silicone polyether emulsion, lauryl alcohol, and calcium stearate.
[0015] On the other hand, a method for preparing fast-setting and fast-hardening fly ash foamed concrete is provided, comprising the following steps:
[0016] S1. According to the bulk density of the foamed concrete to be prepared, weigh the powder, water and water-reducing agent according to the proportion. The bulk density of the foamed concrete is the mass of the powder.
[0017] S2. Add the weighed powder and water-reducing agent to the mixer and mix them into a uniform mixture.
[0018] S3. Add foaming agent and water required for foaming to the foaming machine to produce foam; wherein the water required for foaming is not included in the water weighed in S1, and the mass of the water required for foaming is determined according to the type of foaming agent;
[0019] S4. Add the water weighed in S1 to the mixture and stir to form a slurry;
[0020] S5, according to formula V 泡 =1-M / ρ 料 Calculate the volume V of foam added. 泡 , with a volume of V 泡 The foam is added to the slurry and stirred for 3-4 minutes to obtain foam slurry. M is the sum of the mass of powder and water in the foamed concrete, and ρ 料 This refers to the density of the foamed concrete slurry.
[0021] S5. Pour the foam slurry into the mold and cure it in the natural environment for 24 hours. After demolding, cure it in the natural environment for 2 days.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention relates to a dicalcium silicate-calcium oxide composite cementitious material calcined at 1200-1250℃, wherein the size of dicalcium silicate is 1μm, while the size of dicalcium silicate in traditional silicate cement clinker exceeds 10μm. The smaller size is beneficial to C2S hydration and hardening, thereby improving the strength of foamed concrete. Furthermore, the size of CaO in the dicalcium silicate-calcium oxide composite cementitious material is about 10μm, which has a fast dissolution rate, generates Ca(OH)2 gel, releases a large amount of heat, promotes slurry thickening, and stabilizes air bubbles.
[0024] 2. Compared with traditional silicate cement, the dicalcium silicate-calcium oxide composite cementitious material of the present invention has a lower calcination temperature and lower energy consumption, and the production of foamed concrete is green and low-carbon.
[0025] 3. Under normal conditions in the presence of gypsum dihydrate, the hydration of CA and CA2 in aluminate cement produces ettringite and alumina gel. The chemical reaction equations are as follows:
[0026] 3CA + 3CaSO4·2H2O + nH2O → AFt (ettringite) + 4Al(OH)3;
[0027] 3CA2 + 3CaSO4·2H2O + mH2O → AFt (calcite) + 10Al(OH)3.
[0028] The presence of Al(OH)3 leads to significant drying shrinkage in aluminate cement during later stages. However, in this invention, the CaO in the dicalcium silicate-calcium oxide composite cementitious material rapidly hydrates to Ca(OH)2. In the presence of Ca(OH)2 and gypsum dihydrate, the aluminate gel produced during the hydration of aluminate cement will generate AFt, as shown in the following chemical reaction equation:
[0029] Al(OH)3 + 3CaSO4·2H2O + 3Ca(OH)2 + bH2O → AFt (ettringite).
[0030] The synergistic hydration of dicalcium silicate-calcium oxide composite cementitious material and aluminate cement in this invention can fully utilize aluminum-containing minerals to generate AFt, which on the one hand promotes the setting and hardening of foamed concrete, and on the other hand reduces shrinkage. In addition, due to the consumption of aluminum binder in the system, the hydration of CA and CA2 minerals can be promoted, thereby improving the strength of foamed concrete.
[0031] 4. Since fly ash mainly contains Al2O3 and SiO2 glass, the depolymerization rate of fly ash glass is highly sensitive to temperature. The CaO in the dicalcium silicate-calcium oxide composite cementitious material generates a large amount of heat during digestion. Combined with the rapid formation of AFt in the system, these factors all contribute to the formation of AlO2 in the fly ash glass. - The dissolution of fly ash makes the glassy network structure of fly ash easily activated, increasing its pozzolanic activity and improving the strength of foamed concrete. Attached Figure Description
[0032] Figure 1 This is a SEM image of the dicalcium silicate-lime composite cementitious material of the present invention. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0034] Example 1
[0035] As a preferred embodiment of the present invention, the fast-setting and fast-hardening fly ash foamed concrete of this embodiment includes powder, water, water-reducing agent and foaming agent.
[0036] In this embodiment, the powder comprises 30 wt% dicalcium silicate-lime composite cementitious material, 5 wt% aluminate cement clinker, 5 wt% dihydrate gypsum, and 60 wt% fly ash by weight percentage.
[0037] In this embodiment, the water-to-material ratio is 0.3.
[0038] In this embodiment, the dosage of polycarboxylate superplasticizer is 0.8 wt‰ of the powder mass.
[0039] In this embodiment, the slurry density of the prepared rapid-setting and rapid-hardening fly ash foamed concrete is 1900 kg / m³. 3 .
[0040] In this embodiment, the mineral composition of the dicalcium silicate-lime composite cementitious material includes: C2S: 62wt%, CaO: 30wt%, C3A: 5wt%, C4AF: 3wt%.
[0041] In this embodiment, the dicalcium silicate-lime composite cementitious material is made by calcining low-grade limestone and waste soil cake at high temperature (1230℃, 45 min). The clinker obtained after calcination is then ground to obtain a specific surface area of 350 kg / m². 2 The mass ratio of low-grade limestone and waste soil briquettes in the dicalcium silicate-lime composite cementitious material is calculated according to the mineral composition of the dicalcium silicate-lime composite cementitious material: C2S: 62wt%, CaO: 30wt%, C3A: 5wt%, C4AF: 3wt%, and the Bogle formula: the mass ratio of low-grade limestone to waste soil is 8:2.
[0042] In this embodiment, the mineral composition of the aluminate cement clinker includes: CA: 49wt%, CA2: 23wt%, C2AS: 28wt%, and alkalinity coefficient A. m It is 1.0.
[0043] In this embodiment, the preparation method of rapid-setting and rapid-hardening fly ash foamed concrete is as follows:
[0044] S1, Prepare a bulk density M of 400 kg / m³ 3 For foamed concrete, the powder, water, and water-reducing agent are weighed according to the mixing ratio.
[0045] S2. Add the weighed powder and water-reducing agent to the mixer and mix them into a uniform mixture.
[0046] S3. Add foaming agent and water required for foaming to the foaming machine to produce foam;
[0047] S4. Add the water weighed in S1 to the mixture and stir to form a slurry;
[0048] S5, according to formula V 泡 =1-M / ρ 料 Calculate the volume V of foam added. 泡 It is 0.73m 3 0.73m 3 Add the foam to the slurry and stir for 3 minutes to obtain foam slurry.
[0049] Step 6: Pour the obtained foam slurry into the mold and cure it in the natural environment for 24 hours. After demolding, cure it in the natural environment for 2 days.
[0050] Example 2
[0051] As a preferred embodiment of the present invention, the fast-setting and fast-hardening fly ash foamed concrete of this embodiment includes powder, water, water-reducing agent and foaming agent.
[0052] In this embodiment, the powder comprises 26 wt% dicalcium silicate-lime composite cementitious material, 12 wt% aluminate cement clinker, 12 wt% dihydrate gypsum, and 50 wt% fly ash by weight percentage.
[0053] In this embodiment, the water-to-material ratio is 0.24.
[0054] In this embodiment, the dosage of polycarboxylate superplasticizer is 1.2 wt‰ of the powder mass.
[0055] In this embodiment, the slurry density of the prepared rapid-setting and rapid-hardening fly ash foamed concrete is 2000 kg / m³. 3 .
[0056] In this embodiment, the mineral composition of the dicalcium silicate-lime composite cementitious material includes: C2S: 50wt%, CaO: 36wt%, C3A: 10wt%, C4AF: 4wt%.
[0057] In this embodiment, the dicalcium silicate-lime composite cementitious material is made by calcining low-grade limestone and waste soil cake at high temperature (1250℃, 20min). The clinker obtained after calcination is then ground to obtain a specific surface area of 330kg / m². 2 The mass ratio of low-grade limestone and waste soil briquettes in the dicalcium silicate-lime composite cementitious material is calculated according to the mineral composition of the dicalcium silicate-lime composite cementitious material: C2S: 50wt%, CaO: 36wt%, C3A: 10wt%, C4AF: 4wt%, and the Bogle formula. The mass ratio of low-grade limestone to waste soil is 8:2.
[0058] In this embodiment, the mineral composition of the aluminate cement clinker includes: CA: 31wt%, CA2: 36wt%, C2AS: 33wt%, and alkalinity coefficient A. m It is 0.95.
[0059] In this embodiment, the preparation method of rapid-setting and rapid-hardening fly ash foamed concrete is as follows:
[0060] S1, Prepare a bulk density M of 400 kg / m³ 3 For foamed concrete, the powder, water, and water-reducing agent are weighed according to the mixing ratio.
[0061] S2. Add the weighed powder and water-reducing agent to the mixer and mix them into a uniform mixture.
[0062] S3. Add foaming agent and water required for foaming to the foaming machine to produce foam;
[0063] S4. Add the water weighed in S1 to the mixture and stir to form a slurry;
[0064] S5, according to formula V 泡 =1-M / ρ 料 Calculate the volume V of foam added. 泡 It is 0.752m 3 0.752m 3 Add the foam to the slurry and stir for 4 minutes to obtain foam slurry.
[0065] Step 6: Pour the obtained foam slurry into the mold and cure it in the natural environment for 24 hours. After demolding, cure it in the natural environment for 2 days.
[0066] Example 3
[0067] As a preferred embodiment of the present invention, the fast-setting and fast-hardening fly ash foamed concrete of this embodiment includes powder, water, water-reducing agent and foaming agent.
[0068] In this embodiment, the powder comprises 28 wt% dicalcium silicate-lime composite cementitious material, 9 wt% aluminate cement clinker, 9 wt% dihydrate gypsum, and 54 wt% fly ash by weight percentage.
[0069] In this embodiment, the water-to-material ratio is 0.27.
[0070] In this embodiment, the dosage of polycarboxylate superplasticizer is 1.0 wt‰ of the powder mass.
[0071] In this embodiment, the slurry density of the prepared rapid-setting and rapid-hardening fly ash foamed concrete is 1950 kg / m³. 3 .
[0072] In this embodiment, the mineral composition of the dicalcium silicate-lime composite cementitious material includes: C2S: 56wt%, CaO: 33wt%, C3A: 7wt%, C4AF: 4wt%.
[0073] In this embodiment, the dicalcium silicate-lime composite cementitious material is made by calcining low-grade limestone and waste soil cakes at high temperature (1200℃, 60 min). The clinker obtained after calcination is then ground to obtain a specific surface area of 340 kg / m². 2 The mass ratio of low-grade limestone and waste soil briquettes in the dicalcium silicate-lime composite cementitious material is calculated according to the mineral composition of the dicalcium silicate-lime composite cementitious material: C2S: 56wt%, CaO: 33wt%, C3A: 7wt%, C4AF: 4wt%, and the Bogle formula. The mass ratio of low-grade limestone to waste soil is 8:2.
[0074] In this embodiment, the mineral composition of the aluminate cement clinker includes: CA: 40wt%, CA2: 30wt%, C2AS: 30wt%, and alkalinity coefficient A. m It is 0.97.
[0075] In this embodiment, the preparation method of rapid-setting and rapid-hardening fly ash foamed concrete is as follows:
[0076] S1, Prepare a bulk density M of 400 kg / m³ 3 For foamed concrete, the powder, water, and water-reducing agent are weighed according to the mixing ratio.
[0077] S2. Add the weighed powder and water-reducing agent to the mixer and mix them into a uniform mixture.
[0078] S3. Add foaming agent and water required for foaming to the foaming machine to produce foam;
[0079] S4. Add the water weighed in S1 to the mixture and stir to form a slurry;
[0080] S5, according to formula V 泡 =1-M / ρ 料 Calculate the volume V of foam added. 泡 It is 0.739m 3 0.739m 3 Add the foam to the slurry and stir for 4 minutes to obtain foam slurry.
[0081] Step 6: Pour the obtained foam slurry into the mold and cure it in the natural environment for 24 hours. After demolding, cure it in the natural environment for 2 days.
[0082] Comparative Example 1
[0083] In this comparative example, ordinary silicate cement clinker completely replaced the dicalcium silicate-lime composite cementitious material at a dosage of 28 wt%, and the proportions of the remaining raw materials were the same as in Example 3. The preparation method of the foamed concrete was the same as in Example 3.
[0084] Comparative Example 2
[0085] In this comparative example, sulfoaluminate clinker completely replaced aluminate cement clinker at a dosage of 9 wt%, and the proportions of the remaining raw materials were the same as in Example 3. The preparation method of the foamed concrete was the same as in Example 3.
[0086] Test case
[0087] The foamed concrete samples from Examples 1 to 3 and Comparative Examples 1 to 2 were tested for strength at various ages and 28-day shrinkage rate. The test results are shown in Table 1.
[0088] Table 1. Test results of foamed concrete in each embodiment and comparative example.
[0089] Example 1 1.3 2.3 0.15 Example 2 1.4 2.6 0.13 Example 3 1.3 2.5 0.13 Comparative Example 1 1.0 1.6 0.20 Comparative Example 2 0.8 1.4 0.21
[0090] As shown in Table 1, the 3-day and 28-day compressive strengths of Examples 1-3 are higher than those of the comparative example, exhibiting early strength characteristics. Regarding drying shrinkage, the drying shrinkage rates of all examples are less than 0.2%, while the drying shrinkage rates of the comparative example are higher or greater than 0.2%. Therefore, the fly ash foamed concrete prepared using the dicalcium silicate-lime composite cementitious material, aluminate cement, and dihydrate gypsum system can achieve early strength and low shrinkage.
[0091] Figure 1 This is a SEM image of the dicalcium silicate-lime composite cementitious material of the present invention. Figure 1 As shown, the calcium oxide (CaO) particles in the dicalcium silicate-lime composite cementitious material are popcorn-shaped with a size of about 5-10 μm and have a relatively fast digestion rate; while the dicalcium silicate (C2S) particles are about 1 μm in size and have good hydration activity.
[0092] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.
Claims
1. A fast-setting and fast-hardening fly ash foamed concrete, characterized in that, The mixture includes powder, water, a water-reducing agent, and a foaming agent. The powder comprises the following components by weight percentage: 26-30 wt% dicalcium silicate-lime composite cementitious material, 5-12 wt% aluminate cement clinker, 5-12 wt% dihydrate gypsum, and 50-60 wt% fly ash. The amount of water is calculated based on a water-to-material ratio of 0.24-0.
30. The dosage of the water-reducing agent is 0.8-1.2 wt‰ of the powder mass. The foaming agent is used to prepare foam, and the volume of foam added is based on the bulk density of the foamed concrete. The dicalcium silicate-lime composite cementitious material comprises the following mineral components by mass percentage: C2S: 50-62 wt%, CaO: 30-36 wt%, C3A: 5-10 wt%, C4AF: 3-4 wt%; The dicalcium silicate-lime composite cementitious material is made by calcining low-grade limestone and waste soil cakes at high temperature (1200-1250℃, 20-60 min). The clinker obtained after calcination is then ground to obtain a specific surface area of 330-350 kg / m². 2 The mass of low-grade limestone and waste soil briquettes is calculated based on the mineral composition of the dicalcium silicate-lime composite cementitious material according to the Bouger formula. The aluminate cement clinker comprises the following mineral components by mass percentage: CA: 31~49 wt%, CA2: 23~36 wt%, C2AS: 28~33 wt%.
2. The rapid-setting and rapid-hardening fly ash foamed concrete according to claim 1, characterized in that, The low-grade limestone has a loss on ignition of 40.13±2wt% and comprises the following mineral components by mass percentage: SiO2: 6.04±2wt%, Al2O3: 1.77±0.5wt%, Fe2O3: 0.73±0.5wt%, CaO: 49.00±2wt%, MgO: 1.10±0.5wt%.
3. The rapid-setting and rapid-hardening fly ash foamed concrete according to claim 1, characterized in that, The waste soil has a loss on ignition of 17.00±2wt% and includes the following mineral components by mass percentage: SiO2: 43.60±2wt%, Al2O3: 13.67±2wt%, Fe2O3: 21.51±2wt%, CaO: 1.85±2wt%, MgO: 2.29±2wt%.
4. The rapid-setting and rapid-hardening fly ash foamed concrete according to claim 1, characterized in that, The alkalinity coefficient A of the aluminate cement clinker m It ranges from 0.9 to 1.
0.
5. The rapid-setting and rapid-hardening fly ash foamed concrete according to claim 1, characterized in that, The density of the foamed concrete slurry is 1900~2000 kg / m³. 3 .
6. The rapid-setting and rapid-hardening fly ash foamed concrete according to claim 1, characterized in that, The water-reducing agent is a polycarboxylate water-reducing agent; the foaming agent is one of silicone polyether emulsion, lauryl alcohol, and calcium stearate.
7. A method for preparing rapid-setting and rapid-hardening fly ash foamed concrete according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. According to the bulk density of the foamed concrete to be prepared, weigh the powder, water and water-reducing agent according to the proportion. The bulk density of the foamed concrete is the mass of the powder. S2. Add the weighed powder and water-reducing agent to the mixer and mix them into a uniform mixture. S3. Add foaming agent and water required for foaming to the foaming machine to produce foam; S4. Add the water weighed in S1 to the mixture and stir to form a slurry; S5. According to the formula Calculate the volume of foam added. V 泡 , with a volume of V 泡 Add the foam to the slurry and stir for 3-4 minutes to obtain a foam slurry. M This is the sum of the masses of powder and water in the foamed concrete. ρ 料 The density of the foamed concrete slurry; S5. Pour the foam slurry into the mold and cure it in the natural environment for 24 hours. After demolding, cure it in the natural environment for 2 days.
Citation Information
Patent Citations
High-strength foam concrete and preparation method thereof
CN116177969A
Lightweight thermal insulation foam concrete and preparation method thereof
CN118005350A
Rapid hardening early strength type foam concrete and preparation method thereof
CN105481325A
Preparation method of novel foam concrete
CN115180907A